Comparison in terms of the legal framework of gender equality in education between Malaysia and United States - Han, Haw Ze (2023)
This study aims to analyze the legal frameworks for gender equality in education, comparing Malaysia and the United States. The qualitative method was used in this research involved conducting interviews with four specialists in the laws and regulations associated with gender equality in education.